Perlindungan Hukum Bagi Perempuan Dalam Perspektif Hukum Islam - Nuraini1234; fadila, dea; amelia, bela; berutu, linda; sakina, dini (Tabayyun : Journal Of Islamic Studies, 2023)
Discussions are taking place on Islamic legal viewpoints and women's role in politics. When it came to the prospect of a female president in Indonesia, Islamic political groups were adamant in 1999; however, they have since